Immunization for plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Bananas, rice, tobacco and vegetables are some of the crops that may benefit from a new concept in plant protection. The revolutionary method for crop disease control uses an 'activator' known as CGA 245705 which has been developed by Ciba-Geigy....